Legal Benefits (Utility) According to Hasbi Ash-Shiddieqy (Internalization of Islamic Legal Philosophy in The Compilation of Islamic Law) - Noor Azizah; Fahriansyah Fahriansyah (Scholar Center, 2024)
With the principle of benefit in mind, the law will be dynamic in responding to the dynamics of human life, thus not detached from human life. There is an interconnection between the normativity of law and the historicity of humanity. The method used in this research is the normative research method, which examines the history of law in its development based on the thoughts of Hasbi Ash-Shiddieqy. From this research, it can be concluded that Hasbi, in the field of Islamic Law, introduces the concept of the benefits of Islamic law to the Indonesian public in a balanced manner. Hasbi's thought constructs in the field of benefits are based on: Istihsan, Saddudz Dzari’ah, and Maslahah.